Determination of free malondialdehyde in human serum by high-performance liquid chromatography - Karatas, F; Karatepe, M; Baysar, A (Academic Press Inc Elsevier Science, 2002)
Lipid peroxidation involves the oxidative deterioration of polyunsaturated fatty acids in biomembranes and generates a variety of aldehydic products including malondialdehyde (MDA). To demonstrate the occurrence of lipid peroxidation in biological systems, the production of MDA has been shown to be a relevant indicator. Therefore, we describe a new method for measurement of free malondialdehyde in human serum. A simple, rapid but sensitive method for determination of MDA in human serum was applied to goiter patients and control groups. Patients with goiter had high levels of MDA compared to control groups. Our method is fast and practical for clinical measurements, The detection limit was found to be 1.2 x 10(-8) mol L-1. (C) 2002 Elsevier Science (USA). All rights reserved.
Keywords: HPLC; MDA; serum; goiter